The Influence of Parenting Patterns on Student Learning Motivation at MTs Fadhilah Pekanbaru - Poppy Arista Febriani; Gimin Gimin; Indra Primahardani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is motivated by the phenomenon of low student motivation caused by the parents' parenting role. This study aims to determine whether there is an influence of parenting style on students' learning motivation at MTS Fadhilah Pekanbaru. This study uses a quantitative descriptive method, where the data collection instrument used is a questionnaire with a total of 30 item statement items distributed to 51 respondents. Based on the results of statistical calculations, Fcount (41.546) Ftable (4.04) means that Ha is accepted. Based on the results of the acquisition linear regression equation, namely Y = 10.828 + 0.609X, it means that if the parenting style (X) has increased by 1, then student learning motivation (Y) has increased by 0.609. So that it can be interpreted from the results of the F test that there is an influence between the X variable on the Y variable, meaning that Ha is accepted, namely: There is an influence of parenting style on student learning motivation at MTS Fadhilah Pekanbaru.